Enhancing qur'anic memorization using the talaqqi method assisted by audio-visual media among children aged 5-6 years - Hasibuan, Ria Handayani; Sit, Masganti (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: This research is motivated by the low interest, motivation, and retention of Qur'anic memorization among children aged 5–6 years at Nur Ihsan IFDS Private Islamic Kindergarten in Medan. This issue stems from the use of conventional talaqqi methods, which are less engaging and not aligned with the learning characteristics of early childhood, who tend to understand and retain information more effectively through interactive and stimulating media. Aim : This study aims to improve the ability to memorize Qur'anic verses among children aged 5–6 years through the application of the talaqqi method assisted by audio-visual media at Nur Ihsan IFDS Private Islamic Kindergarten in Medan. Method : This study employed a Classroom Action Research (CAR) approach involving 10 children (5 boys and 5 girls). Data were collected through tests, observations, interviews, and documentation. Result : The results of the study showed a significant improvement in Qur’anic memorization skills. In the pre-cycle phase, the average accuracy of makharijul huruf was 77.06%, and the ability to memorize Surah Ali Imran verse 16 was 81.50%. After Cycle I, these scores increased to 97.43% for makharijul huruf accuracy and 96.50% for memorization ability. The improvement continued in Cycle II, with the average accuracy of makharijul huruf reaching 100% and the memorization ability of Surah Ali Imran verse 16 reaching 99.50%. Overall, there was a 22.50% increase in makharijul huruf accuracy and an 18% increase in memorization fluency from the pre-cycle to Cycle II. Conclusion : It is concluded that the application of the talaqqi method assisted by audio-visual media significantly enhances the ability to memorize Surah Ali Imran verse 16 among children aged 5–6 years, making the learning process more interactive, enjoyable, and effective. This study recommends the optimal use of audio-visual media in early childhood Qur'anic memorization to create an engaging learning environment that aligns with children's characteristics, and as a solution to increase their interest and motivation in memorizing the Qur'an.